(untitled) (CIPEEX, 2025)
Vaccination is an effective and cost-effective policy for preventing and controlling infectious diseases. In Brazil, vaccination coverage continues to grow, despite the challenges of an emerging country. However, a number of factors, such as poor adherence to campaigns, prevent such programs from being as effective as they should be. In this sense, it is necessary to help identify the barriers and challenges that prevent optimal adherence to vaccination. Given this, the present study aims to analyze COVID-19 vaccination coverage and adherence among the adult population in the municipality of Anápolis, Goiás. This is a cross-sectional, descriptive, and quantitative study developed using a semi-structured questionnaire that assessed vaccination coverage, adherence, and knowledge of the COVID-19 vaccine. A total of 136 adults were surveyed, of whom the majority were men (54.25%) aged between 18 and 59 years. Regarding the COVID-19 vaccine, 84.04% knew its function. Adherence to the first and second doses was high (91.48% and 88.29%), but only 28.72% completed the vaccination schedule with booster doses. Thus, the study showed high initial adherence to COVID-19 vaccination among older adults in Anápolis, Goiás, with confidence in the vaccine’s efficacy and safety. However, there was low adherence to booster doses, highlighting challenges such as fear of adverse effects and lack of medical recommendation.